The low density lipoprotein receptor modulates the effects of hypogonadism on diet-induced obesity and related metabolic perturbations - Caterina Constantinou; Diogenis Mpatsoulis; Anastasios Natsos; Peristera-Ioanna Petropoulou; Evangelia Zvintzou; Abdulmaged M. Traish; Peter J. Voshol; Iordanes Karagiannides; Kyriakos E. Kypreos (Journal of Lipid Research, 2014)
Here, we investigated how LDL receptor deficiency (Ldlr−/−) modulates the effects of testosterone on obesity and related metabolic dysfunctions. Though sham-operated Ldlr−/− mice fed Western-type diet for 12 weeks became obese and showed disturbed plasma glucose metabolism and plasma cholesterol and TG profiles, castrated mice were resistant to diet-induced obesity and had improved glucose metabolism and reduced plasma TG levels, despite a further deterioration in their plasma cholesterol profile. The effect of hypogonadism on diet-induced weight gain of Ldlr−/− mice was independent of ApoE and Lrp1. Indirect calorimetry analysis indicated that hypogonadism in Ldlr−/− mice was associated with increased metabolic rate. Indeed, mitochondrial cytochrome c and uncoupling protein 1 expression were elevated, primarily in white adipose tissue, confirming increased mitochondrial metabolic activity due to thermogenesis. Testosterone replacement in castrated Ldlr−/− mice for a period of 8 weeks promoted diet-induced obesity, indicating a direct role of testosterone in the observed phenotype. Treatment of sham-operated Ldlr−/− mice with the aromatase inhibitor exemestane for 8 weeks showed that the obesity of castrated Ldlr−/− mice is independent of estrogens. Overall, our data reveal a novel role of Ldlr as functional modulator of metabolic alterations associated with hypogonadism.